Personality traits, social support, and training transfer The mediating mechanism of motivation to improve work through learning - Kueh, Hua Ng; Rusli, Bin Ahmad (Emerald Publishing Limited, 2018)
Purpose – Substantially few or no known empirical studies have explicitly focused on the higher-order construct of motivation in human resource development (HRD), namely, motivation to improve work through learning (MTIWL) as a mediator linking personality traits and social support to training transfer. Hence, the purpose of this paper is to redress the inadequacy by exploring the role of MTIWL as a mediator on such relationships. Design/methodology/approach – Consistent with positivism, quantitative data based on self-rating were collected from 131 trainees attending management training programs organized by a public sector training provider in Malaysia. Findings – The findings indicate that personality traits (i.e. conscientiousness, extraversion, and agreeableness) and social support (i.e. perceived organizational support and peer support) influenced training transfer via the mediating role of MTIWL. Supervisor support, nonetheless, was not a significant predictor of training transfer through MTIWL. Originality/value – This study focuses on a more holistic motivational construct than simple motivation in HRD. The focus on MTIWL extends the existing understanding of the underlying motivational influences that link dispositional and situational factors to training transfer in occupational settings.